Characterization of Melanoma Cell Lines Resistant to Vemurafenib and Evaluation of Their Responsiveness to EGFR- and MET-Inhibitor Treatment - Dratkiewicz, Ewelina (Int J Mol Sci, 2019)
Constitutively active mutated BRAF kinase occurs in more than 40% of patients suffering from melanoma. To block its activity, a specific inhibitor, vemurafenib, is applied as a therapy. Unfortunately, patients develop resistance to this drug rather quickly. Previously, we demonstrated that pairs of inhibitors directed against EGFR (epidermal growth factor receptor) and MET (hepatocyte growth factor receptor) trigger a synergistic cytotoxic effect in human melanoma cells, and decrease their invasive abilities. In this study, we aimed to generate and characterize melanoma cells resistant to vemurafenib treatment, and then to evaluate the effectiveness of a previously developed therapy in this model. We showed that melanoma cells resistant to the BRAF inhibitor are characterized by a lower proliferation rate and they acquire a spindle-like shape. Using Western Blot, we also noticed increased levels of EGFR, MET, and selected markers of cancer stem cells in generated cell lines. Resistant cells also exhibited increased invasive abilities and elevated proteolytic activity, observed using scratch wound assays and gelatin zymography. Moreover, combination therapy reduced their viability, as measured with a colorimetric cytotoxicity test, and decreased invasiveness. The obtained results validate the application of combination therapy directed against EGFR and MET in melanoma cells resistant to treatment with inhibitors of mutated BRAF.